Program Kampus Mengajar Empat untuk Meningkatkan Kemampuan Literasi dan Numerasi Peserta Didik di SDN Inpres 145 Pampangan - Ashar, Ashar; Munir, Andi Nurzhaahira; Agusalim, Fachril; Taufik, Ilham; Akbar, Fadlan Umarul (Pelita: Jurnal Pengabdian kepada Masyarakat, 2023)
The aim of the Campus Teaching 4 program at SD 145 Pampangan is, of course, to improve students' literacy and numeracy skills through several students from different tertiary institutions. In practice there are several literacy and numeracy programs related to literacy and numeracy collaboration programs implemented with teachers, literacy and numeracy programs with campus teaching groups, literacy and numeracy programs with students inside and outside the classroom, interesting learning during social interaction at school and in implementing literacy and numeracy programs. The measurement results of students are based on the worksheets that have been given. In the literacy program, 3 students got repetition questions and the other students managed to get scores above 70. Furthermore, in the numeration program, the average value obtained was above 70, so there were no repetition questions given to students. Changes and cognitive development experienced by students are increasing, especially in terms of literacy and numeracy, so that it can be said that the programs implemented are successful and also show significant changes for students.